Bis(2,2′-bipyridine)(5,5′-iminoditetrazolato)cadmium(II) 2,2′-bipyridine hemisolvate monohydrate - Lin, Jiao-Min (International Union of Crystallography, 2007)
The title complex, [Cd(C(2)HN(9))(C(10)H(8)N(2))(2)]·0.5C(10)H(8)N(2)·H(2)O, was prepared under hydrothermal reaction conditions. The asymmetric unit contains the cadmium complex, half a 2,2′-bipyridine solvent molecule and a solvent water molecule. The Cd(II) ion is coordinated by four N atoms from two 2,2′-bipyridine ligands and two N atoms from an HBTA(−) anion ligand [where H(2)BTA is N,N-bis(1H-tetrazol-5-yl)amine], forming an octahedral geometry. The complex is linked into a three-dimensional network by O—H⋯N and N—H⋯N hydrogen bonds and by the stacking interactions of rings, with distances of 3.5–3.7 Å between the atoms of two parallel 2,2′-bipyridine rings.